RESILIENSI KELUARGA PASIEN PASCA RAWATAN DI RUMAH SAKIT JIWA PROVINSI JAWA BARAT - Devina Nelviana Pentariputri; Pribowo Pribowo; Aam Muharam (Politeknik Kesejahteraan Sosial (Poltekesos) Bandung, 2021)
Familiy resilience comprises three key processes that help the ability of a family development to face difficult situations. Thus, a family can overcome the difficulties and develop from the difficulties. The aim of this research attempts to assess 1) description of the informant’s identitiy; 2) family’s belief system in viewing a problem; 3) organization’s pattern or relationship runned by the family; 4) communication process in the family; and 5) family’s expectations towards their conditions. The method used to assess this research is descriptive qualitative method and the data sources used are primary and secondary data sources. To determine the data sources, this research uses a purposive technique. The data collection techniques used to assess in this research are 1) in-depth interview; 2) observation; and 3) study documentation. The data validation techniques used in this research are the extension of observation, the consistency of observation, and the triangulation technique. The result of this research shows all families of schizophrenic patients have a different resilience condition.